The Effect of 6-weeks of Practicing Balance Exercises on Developing Agility for Youth Tennis Players - Ali, Sura Mahmoud; Ali, Sama Mahmoud (International Journal of Psychosocial Rehabilitation, 2020)
Objectives: the aims of the study were the preparation of balance exercises to develop the agility for young tennis players, and to identify the effect of practicing balance exercise on developing the agility for young tennis players. Design: an experimental design was used. Setting: Subject was randomly divided into two groups; the control group and the experimental group. Participants: Twenty-four participants were chosen from x Tennis Federation’s Players and their mean age 19.86 ± 1.81 years. Measures: Pre- and post-test included: Planned Agility test. Measures: Pre- and post-test included: Planned Agility test. Results: that there was a significant difference between experimental group and control group in agility. Conclusions: The results showed the benefits of balance exercises on developing agility for youth tennis players.